India the next decade/edited by Manmohan Malhoutra - "Malhoutra, Manmohan (ed.)" (New Delhi, 2006)
Exploring India$1 (Bs growing global importance, this in-depth study offers a wide perspective on the democracy, economy, and society of an ever-evolving nation. s
Keywords: Democracy-India-Forecasting